2021
DOI: 10.46793/kgjmat2103.449s
|View full text |Cite
|
Sign up to set email alerts
|

Optimizations on Statistical Hypersurfaces with Casorati Curvatures

Abstract: In the present paper, we study Casorati curvatures for statistical hypersurfaces. We show that the normalized scalar curvature for any real hypersurface (i.e., statistical hypersurface) of a holomorphic statistical manifold of constant holomorphic sectional curvature k is bounded above by the generalized normalized δ−Casorati curvatures and also consider the equality case of the inequality. Some immediate applications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In recent years, during literature reviews on statistical submanifolds, it has been observed that studies have focused on Chen inequalities ( [5], [6], [15], [53]),Wintgen inequalities ( [8], [25], [44]) and inequalities involving the normalized δ-Casorati curvatures ( [12], [16], [17], [26], [38], [54]).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, during literature reviews on statistical submanifolds, it has been observed that studies have focused on Chen inequalities ( [5], [6], [15], [53]),Wintgen inequalities ( [8], [25], [44]) and inequalities involving the normalized δ-Casorati curvatures ( [12], [16], [17], [26], [38], [54]).…”
Section: Introductionmentioning
confidence: 99%
“…In this reason, the geometric study of Casorati curvatures for submanifolds is new and has many research problems. A couple of optimal Casorati inequalities had been obtained by many distinguished geometers in different ambient space forms (for example, [3,4]). Decu et al have built certain inequalities for statistical submanifolds of Kenmotsu statistical manifolds with constant φ-sectional curvature involving normalized δ-Casorati curvatures and scalar curvature in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Guadalupe and Rodriguez generalized Wintgen's inequality to a real-space surface of arbitrary codimension in the form R m+2 (c), m ≥ 2. After that, Chen extended this inequality to surfaces in a 4-dimensional pseudo-Euclidean space E 4 2 with a neutral metric. In [8], DeSmet, Dillen, Verstraelen, and Vrancken found the DDVV conjecture (called the generalized Wintgen inequality in general) for an isometric immersion of a Riemannian manifold into a real space form.…”
Section: Introductionmentioning
confidence: 99%